Oncogenic Osteomalacia: An Approach to Diagnosis with a Case Report - Dey, Biswajit (J Clin Diagn Res, 2017)
Oncogenic osteomalacia, also known as tumour induced osteomalacia, is a rare paraneoplastic syndrome caused by mesenchymal tumours secreting Fibroblast Growth Factor-23 (FGF-23). The characteristic biochemical findings include hypophosphatemia and low 1,25-dihydroxy vitamin D. The differential diagnosis for hypophosphatemia are varied. We present a case of oncogenic osteomalacia in a 29-year-old female, who presented with complaints of generalized diffuse bone pain and walking difficulty for six months duration. Thus, we have discussed the approach to diagnosis in such a case.